Mathematics
Tricia274
14

solving systems of equations by substitution

+1
(1) Answers
SheliaMifflin

Equation 1)  2x - 3y = -1 Equation 2)  y = x -1 Rearrange equation 2 so that x and y are on the same side. To do so, you subtract x from both sides. 2)  -x + y = -1 1)  2x - 3y = -1 Multiply ALL of equation 2 by 2. 2)  2(-x + y = -1) Simplify. 2)  -2x + 2y = -1 1)  2x - 3y = -1 Add equations together. -y = 0 So, y = 0 Plug in 0 for y in the first equation. 2x - 3y = -1 2x - 3(0) = -1 Simplify. 2x - 0 = -1 2x = -1 Divide both sides by 2. x = -1/2 (-1/2 , 0) ~Hope I helped!~

Add answer